Rare-Earth Geochemistry of Antarctic Diogenites - Masuda, Akimasa; Tanaka, Tsuyoshi; Shimizu, Hiroshi; Wakisaka, Takeshi; Nakamura, Noboru (1979)
P(論文) Rare-earth elements (REE) were determined for seven diogenite samples (four whole rock samples, two separate fractions and one handpicked orthopyroxene sample), prepared from Yamato-74010,-74013,-74037 and -74136. Diogenites, Yamato-74037 and -74136,have positive Ce anomalies of 14 and 17%, respectively. REE distribution has been found to be heterogeneous even in the same sample (Yamato-74010) of the size less than 2g without any apparent distinctions in itself. The Lu contents are generally lower than in diogenites studied by FUKUOKA et al. (1977) and SCHMITT et al. (1963). Unlike diogenites examined by these authors, REE patterns of a large fraction of Antarctic diogenites show marked turning-up toward the lightest REE. Diogenite Yamato-74010 was separated into four fractions, with the special aim of collection of a floating ultrafine-grained fraction. This fraction and a coarse-grained one display contrasting differences in Eu anomaly as well as Na content. Assuming that, in ideally the simplest case, the REE partition coefficient function for orthopyroxene is a logarithmically linear function of difference in atomic number, a function responsible for turning-up towards the lighter REE was evaluated. Regardless of mutually opposite signs, the absolute magnitude of inclination coefficient for this function is similar to that for the function ideally assumed for simple orthopyroxene effect. departmental bulletin paper